(untitled) (ARQUISUR Revista, 2017)
The mail goal of this publication is to propose a reflection on Eladio Dieste’s work from the point of view of digital fabrication. That means, an interpretation of heritage through a critical reading of the means of production employed by the author, based on the digital manufacture of a 1:20 scale model of Capilla Cristo Obrero, with the purpose of promoting the generation of new visions of an emblematic and innovative work, that survives until today.